2020
DOI: 10.5812/iranjradiol.92446
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Gold Nanoparticles and Iodinated Contrast Media in Radiation Dose Reduction and Contrast Enhancement in Computed Tomography

Abstract: Background: Gold nanoparticles with high atomic number and density have good potential to be used as contrast media in computed tomography. Objectives: In this study, we aimed to assess radiation dose and contrast enhancement performance of gold nanoparticles by measuring contrast to noise ratio compared to clinically used iodinated contrast agents at same concentrations. Contrast enhancement was evaluated in different tube voltages and currents. Materials and Methods: First, polyethylene glycol coated gold na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Our results from CT imaging demonstrated that AuNPs’ attenuation factor was directly proportional to AuNP concentration. Studies have proposed that AuNPs could be a good candidate as contrast for CT imaging [ 33 , 34 ]. Our results are in accordance with literature results studying a concentration of contrast from 0 to 1 mM [ 22 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results from CT imaging demonstrated that AuNPs’ attenuation factor was directly proportional to AuNP concentration. Studies have proposed that AuNPs could be a good candidate as contrast for CT imaging [ 33 , 34 ]. Our results are in accordance with literature results studying a concentration of contrast from 0 to 1 mM [ 22 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have proposed that AuNPs could be a good candidate as contrast for CT imaging [ 33 , 34 ]. Our results are in accordance with literature results studying a concentration of contrast from 0 to 1 mM [ 22 , 34 , 35 ]. Previously, studies have reported conflicting results regarding the influence of the size of AuNPs as a contrast agent, but no information was found regarding the shape of AuNPs [ 22 , 33 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Detection of atherosclerosis might be improved by using computed tomography agents, such as gold. CNR (contrast-to-noise ratio) of Au-NPs is greater than the commercially available iodinated agent Visipaque TM [83]. However, CT imaging equipment itself entails radiation exposure, and numerous scans in a short period of time are unlikely to be therapeutically feasible.…”
Section: Indiummentioning
confidence: 99%
“…Since tissues and biological fluids have low attenuation capability, contrasting agents (typically iodine-based media) are required for resolved CT imaging in clinical practice. However, it was found that GNP could provide more efficient X-ray attenuation (5.16 for GNP compared to 1.94 cm 2 /g for iodine, at 100 keV) and they thus hold true promise in CT imaging [ 31 , 32 , 33 ]. Based on this property, targeted gold nanoprobes have been employed to localize cancer using a standard clinical CT scan [ 34 , 35 ].…”
Section: Gold Nanoprobes Enables Computed Tomography Imagingmentioning
confidence: 99%